2012
DOI: 10.1029/2012rg000394
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological feedbacks of deforestation

Abstract: [1] Forest vegetation can interact with its surrounding environment in ways that enhance conditions favorable for its own existence. Removal of forest vegetation has been shown to alter these conditions in a number of ways, thereby inhibiting the reestablishment of the same community of woody plants. The effect of vegetation on an environmental variable along with vegetation susceptibility to the associated environmental conditions may imply a positive feedback: Changes in the internal conditions controlling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 453 publications
(455 reference statements)
3
77
0
Order By: Relevance
“…But this is not the case for periods of trending global fire activity, as during rapid climate change (Prentice et al, 2011) or ecosystem shifts (Runyan et al, 2012), when the fire carbon source and sink are out of balance and atmospheric CO 2 concentrations are affected on a long-term basis . Anthropogenic changes to land cover can also alter wildfire area burned and emissions (Harrison et al, 2010;Marlon et al, 2008).…”
Section: Fire-lulcc Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…But this is not the case for periods of trending global fire activity, as during rapid climate change (Prentice et al, 2011) or ecosystem shifts (Runyan et al, 2012), when the fire carbon source and sink are out of balance and atmospheric CO 2 concentrations are affected on a long-term basis . Anthropogenic changes to land cover can also alter wildfire area burned and emissions (Harrison et al, 2010;Marlon et al, 2008).…”
Section: Fire-lulcc Interactionsmentioning
confidence: 99%
“…Previous studies have generally concluded that, globally, fires have been reduced by increases in land management over the 20th century (Houghton et al, 1999;Marlon et al, 2008;Yang et al, 2014). However, local-and regionalscale research show vastly different fire responses to land cover change and land management in different ecosystems (Cochrane and Barber, 2009;Archibald et al, 2009;Runyan et al, 2012). Satellite observations of African savannah show that a portion of the decrease in fires that occurred over the first decade of the 21st century resulted from conversion of savannah to croplands (Andela and van der Werf, 2014).…”
Section: Fire-lulcc Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is particularly suitable for conceptual hydrological models (for a summary see Blöschl et al, 2013c andParajka et al, 2013). However, a drawback of the method is that one usually assumes that the spatial differences in soil parameters apply immediately to the location where land use has been changed, while soils can take decades to respond to land use changes (Runyan et al, 2012).…”
Section: (Iii) Trading Space For Timementioning
confidence: 99%
“…Finally, the inhomogeneous distribution of forcing from surface albedo changes and short-lived trace gas and aerosol species could lead to non-additive (A. D. and highly variable local climate responses . Therefore, we use the RF for our assessment of global-scale climate impacts and acknowledge the limits of the RF concept for predicting the diverse and often local impacts of land use (Betts, 2008;Runyan et al, 2012).…”
Section: Uncertaintymentioning
confidence: 99%